The influence of regional head candidates quality towards political participation of society in the local election - RATNIA SOLIHAH; YUSA DJUYANDI; MUDIYATI RAHMATUNNISA (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: This study aims to analyse how the calibre of the candidates running for regional heads affects voter turnout in local elections.Method: Interviews and careful observation were used as part of this study’s qualitative methodology. Primary and secondary sources were used to compile the data. Because of its interpretive and semantic compatibility with the proposed research problems, this research strategy has been chosen and is considered appropriate.Findings: The democratic process in Indonesia relies heavily on voter turnout. Voter turnout is a good indicator of how politically engaged a community is, so when it rises, so does the quality of our democratic system. Several factors, including the calibre of the candidates running for the regional head, can influence voter turnout.Implications/Novel Contribution: Multiple studies and surveys have failed to uncover any literature on the effect of candidate quality on voter turnout, and this lack of knowledge extends to Indonesia. The research community, therefore, agrees that this essay contributes something new to the scientific discourse.